Effects of Different Nutritional Conditions on the Growth and Reproduction of Nilaparvata lugens (Stål) - Kang, Kui; Cai, Youjun; Yue, Lei; Zhang, Wenqing (Frontiers in Physiology, 2022)
Growth and reproduction are the two most basic life processes of organisms and the distribution of energy in these processes is a core issue of the life history of organisms. Nilaparvata lugens (Stål), the brown planthopper (BPH), is a single-feeding rice pest. In the present study, this species was used as a model for testing the effects of nutritional conditions on various growth and reproduction indicators. First, the third-instar nymphs were fed with three different concentrations (100, 50, and 25%) of artificial diet until the second day of adulthood. The results showed that as the nutrient concentration decreased, the body development and oviposition of BPH were hindered. The total lipid content in the fat bodies was also significantly reduced. RT-PCR analysis showed compared to the 100% concentration group, the expression levels of vitellogenin (Vg) genes in the fifth-instar nymphs, adults, and in different tissues (ovary, fat body, and other tissues) were significantly decreased in the 50 and 25% treatment groups. Western blot analysis showed that Vg protein expression was highest in the 100% group, followed by the 50% group, with no expression in the 25% group. These results indicate that growth and reproduction in the BPH are regulated by, or correlated with, nutrient concentration. This study is of great significance as it reveals the adaptive strategies of the BPH to nutritional deficiencies and it also provides valuable information for the comprehensive control of this pest.